Enhancing audiology students’ understanding of person-centered care: insights from an multi-national virtual student conference - Mahomed-Asmail, Faheema; Nicholson, Nannette; Metcalfe, Louise; Rutherford, Cherilee; Alet Graham, Marien; Watson, Victoria; Regan, Catherine; Hussain, Saira (International journal of audiology, 2025)
This project sought to investigate the impact of a multi-national peer learning initiative in facilitating a student-led conference on person-centred care (PCC). The primary objective was to assess students' comprehension of PCC elements before and after engaging in the opportunity, with a concurrent evaluation of the efficacy of the opportunity. A mixed-methods study protocol was followed. Following the conference, participants completed a four-part survey including (a) demographics, (b) retrospective pre-post Likert scale, (c) Likert rating of conference experience and (d) five open-ended questions. One hundred and four participants (92.4% female) with a mean age of 21 years (0.07 SD) participated in the study. A significant difference in awareness pre-post conference was demonstrated across all topics (WSR, p < 0.001) with participants satisfied with the conference. Qualitative analysis revealed three main themes: (a) application of PCC; (b) perspectives of PCC; and () barriers to PCC; with nine sub-themes. The conference was beneficial in enhancing students' awareness of topics and principles of PCC. Innovative pedagogical approaches should be considered in order to enhance healthcare education allowing future clinicians to better meet the dynamic needs of their clients.